2000
DOI: 10.1161/01.atv.20.3.611
|View full text |Cite
|
Sign up to set email alerts
|

Altered Flow–Induced Arterial Remodeling in Vimentin-Deficient Mice

Abstract: Abstract-The endothelial cytoskeleton plays a key role in arterial responses to acute changes in shear stress. We evaluated whether the intermediate filament protein vimentin is involved in the structural responses of arteries to chronic changes in blood flow (BF). In wild-type mice (Vϩ/ϩ) and in vimentin-deficient mice (VϪ/Ϫ), the left common carotid artery (LCA) was ligated near its bifurcation, and 4 weeks later, the structures of the occluded and of the contralateral arteries were evaluated and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 49 publications
5
82
0
Order By: Relevance
“…28 In the present study, overexpression of eNOS in the endothelium reduced neointimal and medial thickening but did not affect the reduction in vessel diameter. The mechanisms of vascular constriction in this model are unclear, and so far, only the participation of the cytoskeleton 29 and the role of iNOS detected in the adventitia and the outer layer have been suggested. 30 Further studies are needed to clarify the mechanisms, particularly the role of iNOS-derived NO, of the reduction in vascular diameter associated with the cessation of blood flow in this model.…”
Section: Discussionmentioning
confidence: 91%
“…28 In the present study, overexpression of eNOS in the endothelium reduced neointimal and medial thickening but did not affect the reduction in vessel diameter. The mechanisms of vascular constriction in this model are unclear, and so far, only the participation of the cytoskeleton 29 and the role of iNOS detected in the adventitia and the outer layer have been suggested. 30 Further studies are needed to clarify the mechanisms, particularly the role of iNOS-derived NO, of the reduction in vascular diameter associated with the cessation of blood flow in this model.…”
Section: Discussionmentioning
confidence: 91%
“…When blood flow increases chronically, the endothelium triggers a remodeling of the arterial wall with diameter enlargement and hypertrophy. This phenomenon is facilitated by the genetic absence of the intermediate filaments, vimentin or desmin 7,8 suggesting that intermediate filaments stabilize arterial cell shape and oppose the remodeling process. Nevertheless, other proteins such as dystrophin are important in the flow sensing process after either short-or long-term simulation 6,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, since the first study published by Collucci-Guyon and collaborators [3], a few studies conducted with these mice or using different cell culture models derived from vim -/-mice have indicated that vimentin can play an important role. For example, reduction of renal mass was found to be lethal in vim -/-mice, whereas no lethality was observed in littermate controls [4]; cerebellar defects and impaired motor coordination were noted in vim -/-mice; vimentin was implicated in diameter and wall mass changes during flow-induced arterial remodelling [5], and impaired wound healing in both embryonic and adult mice [6] was established using these mice. Curiously, vimentin was not essential for efficient tumour growth and differentiation in vivo [7].…”
Section: Introductionmentioning
confidence: 99%